Antimicrobial Properties of Some Important Medicinal Plants (AYUSHDHARA, 2024)
Plants have been used for thousands of years to enrich and preserve food, cure ailments, and prevent infections, including epidemics. Medicinal plants have played an important role in the regeneration of deteriorating diseases caused by microbial infections., also to prevent from spreading of infectious disease. Furthermore, medicinal plants provide a valuable resource for potentially beneficial compounds for the development of novel chemotherapeutic drugs, which have significantly contributed to human health and well-being. Plant-derived products have the potential to regulate microbial growth in many different kinds of conditions. In the particular context of infection control, several studies have attempted to characterize the chemical constitute of these plant antimicrobial compounds and the processes behind microbial growth suppression, either in isolation or in combination with traditional antimicrobials. Such works should be brought to the attention of every concerned person. The current paper is an attempt to provide a review of some these kinds of plants.